Utilization of the Navien distal intracranial catheter in 78 cases of anterior circulation aneurysm treatment with the Pipeline embolization device. (20th March 2013) - Colby, Geoffrey P; Lin, Li-Mei; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Background: Endovascular treatment of intracranial aneurysms relies on coaxial catheter support systems to provide safe and stable access. Large-bore distal intracranial catheters have become necessary for aneurysm treatment with flow diverting devices including the Pipeline embolization device (PED). These catheters must accommodate 0.027 inch microcatheters, be supple enough to track distally and be able to provide sufficient support for manipulations required for PED deployment. Methods: A single-center aneurysm database was reviewed to identify patients who underwent anterior circulation aneurysm embolization with the PED while using the Navien distal intracranial catheter. Data were collected regarding the equipment used, cervical internal carotid artery (ICA) tortuosity, intraprocedural Navien positions and periprocedural complications. Results: The Navien catheter (5 Fr, 0.070 inch outer diameter, 0.058 inch inner diameter, 115 cm) was used in 78 cases of anterior circulation PED. It was tracked into position over a Marksman microcatheter in 76 of the 78 cases (97%). The final catheter tip position was in the cervical ICA (1/78, 1%), petrous ICA (23/78, 30%), proximal cavernous ICA (48/78, 62%), distal cavernous/clinoidal ICA (3/78, 4%), supraclinoid ICA (2/78, 2%) and the M1 segment (1/78, 2%). In each case the catheter was tracked to its desired position (100% clinical success) despite significant proximal vessel tortuosity in 34 cases (44%). No clinically significant catheter-related complications occurred. Conclusions: The Navien intracranial catheter is an important component of the triaxial system for embolization of cerebral aneurysms with the PED. This catheter is highly trackable to distal positions, atraumatic and provides sufficient support for the microcatheter manipulations used during typical PED deployments.